Metastasis of Colorectal Cancer - Beauchemin, Nicole; Huot, Jacques; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Colorectal cancer is the third most common cancer worldwide, and in many parts of the western world, it is the second leading cause of cancer-related deaths. This book covers colon cancer metastasis from the most fundamental aspects to clinical practice. Major topics include physiopathology, genetic and epigenetic controls, cancer initiating cells, epithelial-mesenchymal transition, growth factors and signalling, cell adhesion, natures of liver metastasis, angiogenesis and lymphangiogenesis, inflammatory response, prognostic markers, sentinel node and staging, and finally diagnosis and treatment. Each chapter has been contributed by leaders in the field. A key feature is that it connects with a large readership including students, fundamentalists and clinicians. Another specific feature of the book is that the chapters are written in a didactic and illustrative fashion. These characteristics coupled with the choice of the topics and authors, makes this book a reference in the field. It represents an essential acquisition for medical libraries, clinicians as well as medical and graduate students.
The Metastatic Process: An Overview -- Physiopathology of Colorectal Metastasis -- The Genetics of Colorectal Cancer -- Epigenetics of Colorectal Cancer -- Cancer-Initiating Cells in Colorectal Cancer -- Epithelial-Mesenchymal Transition in Colorectal Cancer -- Cell Adhesion Molecules in Colon Cancer Metastasis -- Epithelial Cell Signalling in Colorectal Cancer Metastasis -- Angiogenesis and Lymphangiogenesis in Colon Cancer Metastasis -- Role of the Host Inflammatory Response in Colon Carcinoma Initiation, Progression and Liver Metastasis -- Molecular Prognostic Markers in Colon Cancer -- The Sentinel Lymph Node and Staging of Colorectal Cancer -- Treatment of Colorectal Cancer -- Diagnosis and Treatment of Rectal Cancer -- Future Directions.
Keywords: Medicine; Cancer research; Antibodies; Molecular biology; Oncology; Pathology; Biomedicine; Cancer Research; Oncology; Molecular Medicine; Antibodies; Pathology; Electronic books